Understanding Physicians’ Perceptions of Patient-Identified Barriers to Osteoporosis Medication Initiation: A Cognitive Mapping Approach - Qu H; Silverman SL; Shewchuk RM; Curtis JR; Austin S; Greenspan SL; Nieves JW; Outman RC; Warriner AH; Watts NB; Saag KG (Dove Medical Press, 2022)
Haiyan Qu,1 Stuart L Silverman,2 Richard M Shewchuk,1 Jeffrey R Curtis,3 Shamly Austin,4 Susan L Greenspan,5 Jeri W Nieves,6 Ryan C Outman,3 Amy H Warriner,3 Nelson B Watts,7 Kenneth G Saag3 1Department of Health Services Administration, University of Alabama at Birmingham, Birmingham, AL, USA; 2Cedars-Sinai, Los Angeles, CA, USA; 3Department of Medicine, University of Alabama at Birmingham, Birmingham, AL, USA; 4Research, Development, & Analytics, Highmark Wholecare, Pittsburgh, PA, USA; 5Division of Geriatric Medicine, University of Pittsburgh, Pittsburgh, PA, USA; 6Department of Epidemiology, Columbia University, New York, NY, USA; 7Mercy Health, Cincinnati, OH, USACorrespondence: Haiyan Qu, Department of Health Services Administration, University of Alabama at Birmingham, SHPB 580D, 1716 9th Ave. S., Birmingham, AL, 35294-1212, USA, Tel +1 205996-4940, Email hyqu@uab.eduObjective: Interventions to initiate medication and increase adherence for postmenopausal women who have had a fragility fracture were not always successful. The purpose of this study was to derive an empirical framework for patient-identified barriers to osteoporosis medication initiation and adherence from physician experts.Methods: A cognitive mapping approach involving nominal group technique (NGT) meetings and a card sorting and rating task were used to obtain formative data. We first conducted four NGT meetings with 18 women patients who were not on osteoporosis treatment to identify barriers to osteoporosis medication, then invited 27 osteoporosis physicians to sort and rate 25 patients identified barriers. Descriptive analysis, multidimensional scaling analysis, and hierarchical cluster analysis were applied for data analysis.Results: A two-dimensional five-cluster cognitive map was derived to provide an organizational framework for understanding patients perceived barriers to medication initiation and adherence. The five clusters were concerns about side effects, experience of side effects, lifestyle changes, medication access and complexity, and patient uncertainty about treatment and trust in the provider. The two dimensions were interpreted as internal to patients (X-axis) and external to patients (Y-axis).Conclusions/Implications: Views of patients solicited in a structured format provided directions to help in designing interventions to improve osteoporosis medication initiation and adherence.Keywords: nominal group technique, cognitive mapping, patient barriers, osteoporosis treatment, medication initiation, medication adherence